US presidential elections and implied volatility: The role of political uncertainty - Goodell, John W.; Vähämaa, Sami (Journal of Banking & Finance, 2013)
This paper focuses on the effects of political uncertainty and the political process on implied stock market volatility during US presidential election cycles. Using monthly Iowa Electronic Markets data over five elections, we document that stock market uncertainty, as measured by the VIX volatility index, increases along with positive changes in the probability of success of the eventual winner. The association between implied volatility and the election probability of the eventual winner is positive even after controlling for changes in overall election uncertainty. These findings indicate that the presidential election process engenders market anxiety as investors form and revise their expectations regarding future macroeconomic policy.